Effects of Phonological Consistency and Semantic Radical Combinability on N170 and P200 in the Reading of Chinese Phonograms - Hsu, Chun-Hsien; Wu, Ya-Ning; Lee, Chia-Ying (Frontiers in Psychology, 2021)
Studies have suggested that visually presented words are obligatorily decomposed into constituents which could be mapped to language representations. The present study aims to elucidate the extent to which orthographic processing of one constituent affects the other and vice versa during a word recognition task. Chinese orthographic system has characters representing syllables and meanings instead of suffixation roles, and the majority of Chinese characters are phonograms that can be further decomposed into a phonetic radical and a semantic radical. We propose that the effect of semantic radical combinability indexed by semantic radicals and the effect of phonological consistency indexed by phonetic radicals would interact with each other during the reading of Chinese phonograms. Twenty-six right-handed native Chinese speakers were recruited to the study. Participants were presented with phonograms divided into four conditions in accordance with their semantic radical combinability (large vs. small) and phonological consistency (high vs low). EEG signals were recorded throughout the process. Our results show that while reading phonograms, there is an interaction effect between phonological consistency and semantic radical combinability on the right hemisphere N170 activity. That is, semantic radical combinability influenced the right hemisphere N170 during the process of low consistency character reading but not high consistency character reading. On the other hand, the left hemisphere N170 revealed a larger activity during the reading of high consistency characters and was not affected by radical combinability. In addition, while low consistency characters revealed a larger P200 than high consistency characters, the semantic radical combinability effect on P200 was only significant when participants were reading high consistency characters but not low consistency characters. These results provide new information about how ERPs are involved in word recognition within the context of interaction among orthographic and phonological dimensions.